Multiple Micronutrient Supplementation on Hemoglobin Levels among Second-Trimester Pregnant Women - Munazah Alya Zavirah; Reny Retnaningsih; Sulistiyah Sulistiyah (Sarana Ilmu Indonesia (Salnesia), 2026)
Anemia during pregnancy remains a major maternal health concern, particularly in the second-trimester when physiological hemodilution may reduce hemoglobin levels. Iron-folic acid (IFA) supplementation is the standard intervention for preventing and treating maternal anemia; however, multiple micronutrient supplementation (MMS) has been proposed as a potentially more comprehensive approach due to its broader nutrient content. This study aimed to compare the effectiveness of MMS and IFA in improving hemoglobin levels among second-trimester pregnant women. A quasi-experimental pretest-posttest non-equivalent control group design was conducted among 34 pregnant women. Participants were selected using purposive sampling and assigned to either the MMS group (n=17) or the IFA group (n=17). Hemoglobin levels were measured before and after the intervention using the EasyTouch GCHb point-of-care device. Data were analyzed using paired t-tests and independent t-test/Welch’s t-test with a significance level of 0.05. Baseline hemoglobin levels were similar in both groups (9.82 g/dL). Following the intervention, mean hemoglobin levels increased to 10.47 g/dL in the IFA group and 11.38 g/dL in the MMS group. The mean increase in hemoglobin was significantly greater in the MMS group (1.56±0.59 g/dL) compared with the IFA group (0.65±0.05 g/dL), with a between-group difference of 0.91 g/dL (95% CI 0.61–1.21; p < 0.001; Hedges' g = 2.14). MMS was significantly more effective than IFA in increasing hemoglobin levels among second-trimester pregnant women. These findings suggest that MMS may provide greater benefits in addressing maternal anemia during pregnancy.